PREVALENCE, PREVENTION, AND WOUND CARE OF PRESSURE INJURY IN STROKE PATIENTS IN THE NEUROLOGY WARD - Rini Riandini; Etika Emaliawati; Ristina Mirwanti (Belitung Nursing Journal, 2018)
Background: Stroke patient has a risk of experiencing pressure injury, which could affect patient’s life and quality of life; therefore, optimum pressure ulcer prevention should be done. Patients experiencing pressure ulcer should be given appropriate care, to prevent infection and worse conditions. Objective: To identify the prevalence, prevention and treatment of pressure injury of stroke patients in the neurological ward. Methods: This research was a quantitative descriptive research using Landelijke Prevalentiemeting Zorgroblemen instrument. The samples were collected using consecutive sampling method with inclusion criteria of stroke patients experiencing paraplegia, which obtained 30 respondents. Data were presented in frequency distribution format. Results: The result showed that the prevalence of pressure injury was 3.3% of degree III and brought from home. Based on risk assessment, 43.3% of patients had a very high risk of getting pressure injury, and 56.7% had changed position, 100% had received nutritional support but 80% of patients had not received health education and 83.3% did not get a pillow on their heels, and 100% did not get pressure injury mattress, massage, moisturizing cream and oil. Treatment of pressure injury was using 0.9% NaCl liquid with hydrocolloid dressing. Conclusion: It can be concluded that there are still some patients experiencing pressure injury and in terms of items of pressure injury prevention, which often done is malnutrition prevention, the least are the changes of position in using pillows, and in health education. The one that have never been done are the use of oil, moisturizing cream, massage and pressure air mattress. The injury treatment provided to the patient has been adequate. The suggestion that can be given is the preparation of standard operating procedure, leaflets and the provision of pressure air mattress.